It’s Time for Africa’s Voice in the G-20 - Suruma, Ezra (Recovery or relapse, 2010)
As the next meeting of the G-20 draws near, it is once again appropriate to draw attention to the continued marginalization of Africa in this forum. Africa should not be excluded on the grounds that it is poor and therefore unfi t to sit in the rich man’s club. Africa should be included because there are many issues that will be discussed which affect Africa substantially and therefore require Africa’s participation if they are to have legitimacy in their application to African countries.